Brand Experience, Brand Image, Self-Brand Congruity: Relationship with Brand Loyalty Mediated by Brand Satisfaction (On Gen Z Apple Smartphone Users in Bengkulu City) - Lingga, Nora Elisa (Universitas Bengkulu, 2024)
The primary objective of this study is to investigate the influence of brand experience, brand image, and self-brand congruity, mediated by brand satisfaction, on Generation Z Apple smartphone users in Bengkulu City. The research employed purposive sampling to select participants and collected data through an online questionnaire distributed via social media channels. The sample size for this study consisted of 198 individuals. The analytical method used was Partial Least Squares Structural Equation Modeling (PLS-SEM), executed with SmartPLS version 4 software. The study's findings reveal several significant relationships: brand experience, brand image, and self-brand congruity all positively influences brand satisfaction. Additionally, brand experience and self-brand congruity also contribute to brand loyalty, while brand satisfaction is positively linked to brand loyalty. Notably, the analysis shows that brand image does not directly impact brand loyalty. However, brand satisfaction acts as a mediator in the relationship between brand image and brand loyalty, as well as between self-brand congruity and brand loyalty. Interestingly, brand satisfaction does not mediate the relationship between brand experience and brand loyalty. These findings provide insights into the complex relationship between these factors among Generation Z Apple smartphone users in Bengkulu City, valuable for marketers and practitioners.